2022
DOI: 10.3390/molecules27051547
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition, Insecticidal, Persistence and Detoxification Enzyme Inhibition Activities of Essential Oil of Artemisia maritima against the Pulse Beetle

Abstract: Pulse beetle is the major pests of pulses that cause significant loss to grains leads to unfit for consumption and marketing. Indiscriminate use of synthetic pesticides for the control of pulse beetle (Callosobruchus chinensis and Callosobruchus maculatus) led to insect resistance, pesticide residues on grains which affect consumer’s health and environment. Essential oils (EOs) are good alternatives to synthetics due to their safety to the environment and consumers’ health. The main objective of the present st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 63 publications
2
9
0
Order By: Relevance
“…(2021) , stating that T. minuta oil inhibited the AChE and GST activity against P. xylostella . Similarly, the essential oil from Artemisia maritima inhibited the GST activity against C. chinensis and C. maculatus , as reported previously ( Chauhan et al., 2022 ). However, pure compounds of monoterpenes such as α-bisabolol, 1-8-cineole, carvone, carvacrol, chamazulene, and limonene decreased the AChE and GST activities in insects ( Abdelgaleil et al., 2009 ; Rizvi et al., 2018 ).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…(2021) , stating that T. minuta oil inhibited the AChE and GST activity against P. xylostella . Similarly, the essential oil from Artemisia maritima inhibited the GST activity against C. chinensis and C. maculatus , as reported previously ( Chauhan et al., 2022 ). However, pure compounds of monoterpenes such as α-bisabolol, 1-8-cineole, carvone, carvacrol, chamazulene, and limonene decreased the AChE and GST activities in insects ( Abdelgaleil et al., 2009 ; Rizvi et al., 2018 ).…”
Section: Discussionsupporting
confidence: 86%
“…Inhibition activities of detoxification enzymes [acetylcholinesterase (AChE) and glutathione-S-transferase (GST) were carried out using standard procedures ( Chauhan et al., 2022 ). Based on the toxicity assay report, four different concentrations of ocimene and β-myrcene (5,000, 2,500, 1,250, and 625 ppm) were prepared for detoxification enzyme inhibition activity.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, GST, αand β-esterase activities were reduced by exposure to high concentrations of Cymbopogon flexuosus essential oil in Aedes aegypti L. (Diptera: Culicidae) (Carreño et al, 2018). Similarly, Liao et al (2017), Gao et al (2019), andChauhan et al (2022) reported inhibitory effects of essential oils on insect detoxifying enzymes. The Cymbopogon citratus essential oil significantly reduced detoxifying enzyme activity of larvae of Agrotis ipsilon Hufnagel (Lepidoptera: Noctuidae) (Moustafa et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Detoxification enzyme inhibition activities of leaf, bark extracts, and seed oil of T. sebifera against P. xylostella were performed as per the method followed [ 68 ]. Four different concentrations of leaf, bark extract, and seed oil (0.25, 0.5, 1, and 2%) were selected for enzyme activity assay according to the antifeedant assay described above.…”
Section: Methodsmentioning
confidence: 99%